2022
DOI: 10.1177/15330338221132370
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Prognosis of Multiple Myeloma With Myelomatous Pleural Effusion: A Retrospective Single-Center Study

Abstract: Objectives: Myelomatous pleural effusion is a rare presentation of extramedullary disease in multiple myeloma, which has been reported with dismal prognosis. We aimed to explore whether it has distinctive clinical characteristics and outcomes compared to other anatomic locations of extramedullary involvements. Methods: Multiple myeloma patients diagnosed at our institution from 2010 to 2020 were retrieved retrospectively. In total, 42 pairs of patients with and without extramedullary disease were enrolled, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Extramedullary MM of any type is associated with worse outcomes than MM with intramedullary disease only [ 8 ]. MPE in particular carries a significantly worse prognosis than other forms of extramedullary plasmacytoma, with the exception of CNS extramedullary plasmacytoma, which has the highest mortality [ 9 ]. Prior research indicates a median survival of approximately three to four months from the development of MPE [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extramedullary MM of any type is associated with worse outcomes than MM with intramedullary disease only [ 8 ]. MPE in particular carries a significantly worse prognosis than other forms of extramedullary plasmacytoma, with the exception of CNS extramedullary plasmacytoma, which has the highest mortality [ 9 ]. Prior research indicates a median survival of approximately three to four months from the development of MPE [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pleural effusion of various causes can be found in up to 13% of cases, including parapneumonic, reactive, renal, CHF, TB, and MPE, with MPE rendering a poorer outcome in comparison. A study found median overall survival in MPE was 13.0 months, compared to 37.0 months in other EMD and 60.6 months in MM without EMD, with MPE patients being found to have a higher level of beta 2-microglobulin tumor burden and greater multisite extramedullary lesions [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Myelomatous pleural effusion (MPE) is a possible manifestation of EMD. Although MPE only occurs in <1% of patients with MM, it has been associated with a poorer prognosis than MM alone or combined with EMD in other tissues and a marked decrease in survival from the onset of pleural involvement [ 5 ]. It is therefore clinically important to identify and treat pleural effusions caused by EMD in a timely manner.…”
Section: Introductionmentioning
confidence: 99%
“…As for complex karyotypic abnormalities, MPE in patients with multiple myeloma is associated with high‐risk disease. MPE is associated with poor prognosis and short survival times, with a median between 2.4 to 13 months 9,11,12 …”
Section: Explanationmentioning
confidence: 99%
“…MPE is associated with poor prognosis and short survival times, with a median between 2.4 to 13 months. 9,11,12…”
mentioning
confidence: 99%